2016
DOI: 10.1002/lary.25637
|View full text |Cite
|
Sign up to set email alerts
|

Standardized letters of recommendation and successful match into otolaryngology

Abstract: Objective Historically, narrative letters of recommendation have been utilized in selection of applicants for Otolaryngology residency programs. In the last two application cycles, our specialty adopted a standardized letter of recommendation (SLOR). The intent was to decrease time burden for letter writers and to provide readers with an “objective” evaluation of applicants. The objective of this study is to determine attributes in the SLOR that correlate with matching into a residency program. Study Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…This lack of variability in ratings ultimately prevents differentiation amongst applicants. Similarly, Kimple et al demonstrated that scores for professionalism, procedural skills, research, commitment to otolaryngology, and commitment to academic medicine were not correlated with successful matching . This further questions the utility of the individual domains within the SLOR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of variability in ratings ultimately prevents differentiation amongst applicants. Similarly, Kimple et al demonstrated that scores for professionalism, procedural skills, research, commitment to otolaryngology, and commitment to academic medicine were not correlated with successful matching . This further questions the utility of the individual domains within the SLOR.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, disadvantages of the SLOR became apparent shortly thereafter. These include a lack of variation in ratings, preventing differentiation amongst applicants, and the questionable utility of individual domains within the SLOR . Although the SLOR was arguably developed and implemented to replace the NLOR, the majority of institutions continue to submit both.…”
Section: Introductionmentioning
confidence: 99%
“…The academy transitioned to a standardized recommendation form in 2013 and is one of the most important items noted in the candidate's review . In medical residencies, higher standardized recommendation scores were significantly associated with successful matching . However, the overall average recommendation score was 85.6% and 83.3% for matching and non‐matching candidates respectively, highlighting the questionable value of the recommendations …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…3,4 In medical residencies, higher standardized recommendation scores were significantly associated with successful matching. 5 However, the overall average recommendation score was 85.6% and 83.3% for matching and non-matching candidates respectively, highlighting the questionable value of the recommendations. 5 Whether due to selection bias, exaggeration, or professional pressure, many letters of recommendation are overtly positive, making it difficult to understand a candidate's abilities and discern qualifications in comparison to other applicants.…”
mentioning
confidence: 96%
“…However, although the SLOR has been shown to reduce the time burden for letter writers and readers and provide a more objective description of candidates, the utility of the 10 individual domains within the SLOR remains questionable, particularly in a very competitive applicant pool such as otolaryngology, dermatology, and plastic surgery . In this domain, we question whether the SLOR loses sensitivity as a tool when applicants are more uniformly among the academically elite.…”
Section: Introductionmentioning
confidence: 99%